Trans-Eurasian energy transportation networks and the necessity of regional cooperation - Molchanov, Mikhail A. (2016)
The Central Asia-Transcaspian region is rich in energy resources. However, these resources cannot be fully developed without fostering international cooperation. The ‘pipeline wars’ between competing consortia is not conducive to profit maximization. A cooperative regional regime for oil and gas exploration, extraction, and transportation could help improve the business climate and international security. The existing regional integration organizations with a degree of sway in the area the Eurasian Economic Union and the Shanghai Cooperation Organization still have some way to go to prove their usefulness as true promoters of multilateralism. Regional countries that do not belong to either of the two organizations prefer to cooperate on a bilateral basis and this is also true of member states. Regional coordination is necessary to overcome self-interested, beggar-thy-neighbor behavior by business players and states alike in order to maximize regional welfare.